Psychological security and its relationship to academic achievement in a sample of high school students in Al-Baha region - Al-Zahrani, Shareefah Ahmed Ali; Al-Ghamdi, Saeed Ahmed Al Shwail (Journal of Educational and Psychological Sciences, 2021)
This study aimed at identifying the psychological security and its relationship to the educational attainment of a sample of secondary students in Al Baha Region. The researcher used the associational descriptive approach. The study sample consisted of 450 secondary students in Al Baha Region. The researcher used the psychological security measure of Fahd Dulaim and others 1993. The study resulted in several findings, the most important of which is that the secondary students in Al Baha Region have medium level of psychological security, and a statistically significant relationship at the level of (0.01) between the psychological security level and educational attainment of the secondary students in Al Baha Region. The findings also showed statistically significant differences between the average score of a sample of secondary students in Al Baha Region to the total score of the psychological security measure and its dimensions depending on the collection variable (average); the differences were in favor of the students with (High) average versus the students with (Low and Medium) averages. As well as statistically significant differences between the average score of a sample of secondary students in Al Baha Region to the total score of the psychological security measure and its dimensions depending on the grade variable; the differences were in favor of the third grade students versus the first grade at the dimensions: acceptance, tranquility and the psychological security measure total score; and were in favor of the third grade students versus the first and second grade at the affiliation dimension.
Keywords: Psychological Security; Educational Attainment; Secondary School; Al-Baha University